THE DISEASE PATTERN OF ELDERLY PATIENTS ADMITTED IN THE NEUROLOGY WARD OF HASAN SADIKIN GENERAL HOSPITAL - Millata Azma Basmala; Cep Juli; Paulus Anam Ong; Nushrotul Lailiyya; Lisda Amalia (MNJ (Malang Neurology Journal), 2023)
Background: As life expectancy continues to increase, the elderly population in Indonesia has significantly doubled in the last five decades, making Indonesia a home to 4th largest population of elderly people in Asia. Unlike other age group, there are more challenges in handling older persons due to their increased mortality, morbidity, and disability risks. Objective: We performed this study to understand the disease pattern in elderly patients admitted in the neurology ward of Hasan Sadikin General Hospital. Methods: This was a descriptive cross-sectional study using data from medical resume. We included medical resume of elderly patients admitted in the neurology ward of Hasan Sadikin General Hospital from January 2015 to December 2019. All incomplete, lost, or inaccessible medical resumes were excluded. Results: Among a total of 400 subjects, 210 (52.5%) were males and 190 (47.5%) were females. Young old (59,5%) presented to be the most observed age group. The most frequent diseases of elderly patients seen in this study were ischemic stroke (55.3%), followed by hemorrhagic stroke (19.5%), subarachnoid hemorrhage (5.3%), and tetanus (4.5%). Atherothrombotic subtype (50,6%) of ischemic stroke was seen to be the most frequent. Conclusion: Noncommunicable diseases were the majority of all cases in the elderly with cerebrovascular diseases, such as stroke and subarachnoid haemorrhage, as the most common conditions. It is important to develop efficient hospital-based management strategies particularly for these diseases and intensify early detection and management of risk factors.